2013
DOI: 10.5430/jnep.v3n1p23
|View full text |Cite
|
Sign up to set email alerts
|

Turkish nursing students’ perceptions and experiences of bullying behavior in nursing education

Abstract: Objective: This descriptive study aimed to determine the bullying and harassment experiences of nursing students' in various Nursing Schools in Turkey. The types and frequency of bullying behaviors, the sources of bullying behaviors, and students' emotions towards these experiences were investigated.Methods: Study participants were 370 undergraduate nursing students from four different Turkish Nursing Schools. To estimate bullying at nursing school I used a short version of the Negative Acts Questionnaire that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
1
44
0
3
Order By: Relevance
“…Approximately half of nursing students experienced verbal threats, racism or sexism and more than one third of them witnessed other students being bullied while gaining clinical experience [2]. Another study with 370 undergraduate nursing students in Turkey showed that 60% of them experienced bullying in clinical settings [3]. These findings reflected that nursing students should be considered as a risk group that might tend to be exposed to bullying during their clinical placement.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Approximately half of nursing students experienced verbal threats, racism or sexism and more than one third of them witnessed other students being bullied while gaining clinical experience [2]. Another study with 370 undergraduate nursing students in Turkey showed that 60% of them experienced bullying in clinical settings [3]. These findings reflected that nursing students should be considered as a risk group that might tend to be exposed to bullying during their clinical placement.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies [2,3,18,19] have been conducted to investigate the prevalence of bullying between nursing students and staffs and to examine the impact of bullying on occupational outcomes. However, there were no studies to examine the association between bullying experience and psychological outcomes in Korean nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…A higher score indicates a higher level of bullying experience. Reliability tested in a previous study was higher than .80 [9], and…”
Section: ) Bullying Experiencementioning
confidence: 99%
“…While a growing body of knowledge [4,9,10] supports the asso-701 www.jkan.or.kr Bullying referred as horizontal violence, interpersonal conflict, incivility, mobbing, and intimidation [4,8,11]. In this study, bullying was defined as act of aggression or hostility perpetrated deliberately or unconsciously by one person on one or more and can repeatedly occur in covert or overt ways over a period of time, which are all unwanted by the victim, but clearly cause humiliation, offence, and distress, and that may threaten the performance of the healthcare team and/or cause an unpleasant working environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation